2018
DOI: 10.3390/pharmacy6010017
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Partner Treatment of Chlamydia: A Qualitative Investigation with Prescribers and Community Pharmacists

Abstract: Chlamydia trachomatis is the most frequently-notified sexually transmitted infection in Australia. Effective and timely partner treatment of chlamydia is essential to reduce overall prevalence and the burden of infection. Currently in most of Australia, the only avenue for partner treatment of chlamydia (“standard partner therapy”) is a tedious, and often inconvenient, process. The barriers and facilitators of standard partner therapy, and newer models of accelerated partner therapy (APT), need to be identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“… 37 Studies from England and New Zealand showed many pharmacy users were unaware of the presence of a private consultation area, 54 , 55 especially young people 103 and because sometimes pharmacists did not offer the consultation room to their patients. 58 , 62 , 71 , 79 Privacy problems were also reported when consulting about skin disease, 59 weight management 45 and influenza vaccinations. 69 …”
Section: Resultsmentioning
confidence: 99%
“… 37 Studies from England and New Zealand showed many pharmacy users were unaware of the presence of a private consultation area, 54 , 55 especially young people 103 and because sometimes pharmacists did not offer the consultation room to their patients. 58 , 62 , 71 , 79 Privacy problems were also reported when consulting about skin disease, 59 weight management 45 and influenza vaccinations. 69 …”
Section: Resultsmentioning
confidence: 99%
“…While the previous articles focused on a range of stakeholders, including patients and consumers, two other studies focused on health care practitioners. Wood et al [ 5 ] explored the barriers and facilitators to the implementation of Chlamydia partner treatment in Western Australia from the providers’ perspective. This qualitative study involved interviews with health care professionals involved in standard therapy (general practitioners, nurse practitioners, and sexual health clinicians) and community pharmacists.…”
mentioning
confidence: 99%